(untitled) (Journal of Civil Engineering Researchers, 2023)
Flood drainage ditches serve as critical infrastructure, directing and managing floodwaters to prevent indiscriminate flow, reduce flooding risks, and curb erosion. Vegetation plays a crucial role in enhancing the effectiveness of these ditches. It acts as a natural barrier, mitigating floodwater speed and impact while stabilizing soil and preventing erosion. Furthermore, vegetation aids in water quality improvement by filtering pollutants and nutrients, making it safer for humans, animals, and plants. It also reduces peak flows and attenuates floodwaters, thereby minimizing urban flooding risks. Additionally, the presence of vegetation in floodplains provides extra storage capacity for excess water, supporting floodplain management and biodiversity conservation. The study emphasizes the importance of carefully considering vegetation type, characteristics, and management practices to optimize flood drainage ditch performance. Selection of suitable plant species and morphological optimization significantly enhances drainage capacity and infiltration rates. Proper maintenance and management practices are vital to ensure unimpeded water flow and prevent obstruction.